Biosynthesis of ZnO Nanoparticles from Cnidoscolus aconitifolius Leaf Extract: Structure, Morphology, and Photocatalytic Performance for Methylene Blue and Methyl Orange Degradation by UV Light Irradiation - Sri Wahyu Suciyati; Anisatul Mahmudah; Lusia Prastica; Ayu Aprilia (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Zinc oxide nanoparticles (ZnO NPs) were produced via an environmentally friendly approach using Cnidoscolus aconitifolius leaf extract and subsequently heat-treated at 250°C. The presence of Zn–O vibrations and organic functional groups in the extract was verified by FTIR analysis, while XRD data revealed a wurtzite structure with a mean crystallite dimension of 17.64 nm. SEM images mainly showed round-shaped particles with a band gap energy of 3.29 eV. Assessments of photocatalytic capability indicated substantial degradation of methylene blue (MB, reaching 92.96%), in contrast to diminished degradation of methyl orange (MO, registering 43.93%). This improved effectiveness was attributed to the combined favorable effects of concurrent photocatalytic processes. The kinetic evaluation followed a pseudo-second-order model, yielding rate constants of 0.38 min−1 for MB and 0.064 min−1 for MO. Overall, the green-synthesized ZnO NPs calcined at 250°C exhibit excellent photocatalytic activity, particularly for the degradation of MB.